Konsep Wahyu dalam Islam: Fondasi Ilahi bagi Kehidupan, Pengetahuan, dan Kemanusiaan - Sofiatus Sobriyah; Fajar Ainol Yakin (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
almost all major international religions, especially those often called "semitic religions" (Judaism, Christianity, and Islam) which because of their common history and "lineage", are based entirely on "revelation" and "prophets" to define their lifestyle. ontologically and legally, respectively. Revelation is literally interpreted as a quick sign, it can also be interpreted as something that is revealed, revealed or announced. Revelation is an enlightenment, a proof of reality and an affirmation of truth. It is a clear sign, a proof or indication, meaning or significance, to an observer, to be observed, contemplated and understood. From revelation, ideas, suggestions, thoughts, scientific discoveries, an egalitarian social order, and the discovery of divine truth will emerge, enriching knowledge, guidance, and human welfare as well as liberating shackled thoughts, corals, and emotions and elevating dignity and worth. people who are oppressed by the forces of injustice, tyranny and superstition.